Analisis Common Size pada Perusahaan Advertising, Printing dan Media yang Terdaftar di Bursa Efek Indonesia - Andita, Mirza Putri; Annisa, Mutiara Lusiana (Universitas Serambi Mekkah, 2024)
The research objective is to analyze the company's financial performance using the common size method. The population in the research are manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the 2021-2022 period which operate in the advertising, printing and media sectors. The type of sampling used in this research is purposive sampling. The companies that were the object of research were 16 companies over 2 periods (2021-2022). The research results show that there will be an increase in current assets in 2021 of 88% for the companies Intermedia Capital Tbk and MNC Studios International Tbk. For fixed assets, it can be seen that there was an increase of 91% in LINK Net. Meanwhile, for liability posts on short-term and long-term debt. There was an increase in short-term debt of 96%, namely at the company Intermedia Capital Tbk and an increase in long-term debt of 59% at Mahaka Media Tbk. Meanwhile, for equity posts, there was an increase of 99% in the company MNC Studios International Tbk. Furthermore, the increase in current assets in 2022 will be 84% for the companies Intermedia Capital Tbk and MNC Studios International Tbk. For fixed assets, it can be seen that there was an increase of 92% in LINK Net. Meanwhile, for liability posts on short-term and long-term debt. There was an increase in short-term debt of 93%, namely at the company Surta Citra Media Tbk. Furthermore, there was an increase in long-term debt of 53% at MD Pictures Tbk. Meanwhile, for equity posts, there was an increase of 99% in the company MNC Studios International Tbk. The increase in cost of goods sold in 2021 was 81% for the company Intermedia Capital Tbk. For the gross profit post, it can be seen that there was an increase of 78% in LINK Net. Meanwhile, for the net profit post, there was an increase of 66% for the Mahaka Media Tbk company. The increase in cost of goods sold in 2022 will be 87% for the company Intermedia Capital Tbk. For the gross profit post, it can be seen that there was an increase of 77% in LINK Net. Meanwhile, for the net profit post, there was an increase of 58% for the Mahaka Media Tbk company